#2**+15 **

So your equation looks like \(4 = \frac{2}{3}(p-2)\). What you want to do first is get rid of the fraction cause no one likes fractions. You would do this by multiplying the reciprical which is \(\frac{3}{2}\) (just flip the \(\frac{2}{3}\)). The equation would now look like \(4 * \frac{3}{2} = (p-2)\) Simplify it down to \(6 = (p-2)\). Then add the two to both sides and you would get \(8 = p\). Hope this helped!

SilverAg
Mar 9, 2017

#1**+5 **

4=2/3(p-2)

4 = 2/3p - 4/3 add 4/3 to both sides

5 1/3= 2/3p

16/3 = 2/3p divide both sides by 2/3

p = 16/3 / 2/3

p =16/3 x 3/2

p = 48/6

p = 8

Guest Mar 9, 2017

#2**+15 **

Best Answer

So your equation looks like \(4 = \frac{2}{3}(p-2)\). What you want to do first is get rid of the fraction cause no one likes fractions. You would do this by multiplying the reciprical which is \(\frac{3}{2}\) (just flip the \(\frac{2}{3}\)). The equation would now look like \(4 * \frac{3}{2} = (p-2)\) Simplify it down to \(6 = (p-2)\). Then add the two to both sides and you would get \(8 = p\). Hope this helped!

SilverAg
Mar 9, 2017